1998
DOI: 10.1007/bf03350782
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of polycystic ovary syndrome: Lessons from ovarian stimulation studies

Abstract: In polycystic ovary syndrome (PCOS) the ovary produces markedly increased amounts of both androgens and estrogens in response to gonadotropin stimulation. Distinctive responses of 17-hydroxyprogesterone and androstenedione to ovarian stimulation testing suggest that ovarian hyperandrogenism is a result of dysregulation of theca cell androgen production which is intrinsic to the ovary. The occurrence of hyperestrogenism together with hyperandrogenism in PCOS suggests that whatever the abnormality of local regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…Indeed, some in vitro studies have demonstrated that inhibin stimulates ovarian androgen production. 39 As reported above, a phosphorylation of serine residues of the insulin receptor 15 may be a factor leading to insulin insensitivity and, therefore, compensatory hyperinsulinemia in PCOS women. Interestingly, the same disorder seems to be responsible for the increased activity of the human P450c17 system as well.…”
Section: Shbgmentioning
confidence: 86%
“…Indeed, some in vitro studies have demonstrated that inhibin stimulates ovarian androgen production. 39 As reported above, a phosphorylation of serine residues of the insulin receptor 15 may be a factor leading to insulin insensitivity and, therefore, compensatory hyperinsulinemia in PCOS women. Interestingly, the same disorder seems to be responsible for the increased activity of the human P450c17 system as well.…”
Section: Shbgmentioning
confidence: 86%
“…Hyperandrogenism is the primary clinical manifestation of dysregulation of steroid production in patients with PCOS (Barnes, 1998). LH hypersecretion and hyperinsulinemia synergistically increases androgen production (Jayasena & Franks, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…38 Some of the published reports revealed the effects of vitamin D3 on the regulation of steroidogenesis pathway in human granulosa cells. 41,42 It is determined that androgen excess in hyperandrogenic PCOS women could disturb steroidogenesis pathway which subsequently leads to disruption in follicular development. Disturbance in this process could create ovulatory problems and infertility like that seen in PCOS women.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbance in this process could create ovulatory problems and infertility like that seen in PCOS women. 41,42 It is determined that androgen excess in hyperandrogenic PCOS women could disturb steroidogenesis pathway which subsequently leads to disruption in follicular development. 3,43,44 In the present study, we induced PCOS mice model by DHEA to mimic the human anovulatory PCOS and investigated the mechanism of action of vitamin D3 on steroidogenesis process in granulosa cells of the polycystic ovary.…”
Section: Recent Comprehensive Reports On the Role Of Vitamin D In Fermentioning
confidence: 99%